Healthy From An Early Age : Lecturers And Students Woking Together Through Campus And Family Synergy To Improve Child Nutrition At Al – Hikmah Sukaraya Islamic Early Childhood Education Center - Efri Manda Sari Hasibuan; Aidila Syafitri; Phadilla Putri; Ade Armayani; Nurhayati Nurhayati; Jahidatun Nisa (International Journal of Community Service Implementation, 2025)
Community service is the implementation of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) which aims to make a real contribution to improving the quality of life of the community. This community service activity was carried out by lecturers and students as a form of synergy between the campus and families in an effort to improve the nutrition of early childhood. The location of the activity was at the Al-Hikmah Sukaraya Islamic Early Childhood Education Center with the main targets being the parents of students and early childhood educators. Nutrition problems in early childhood are still commonly found, including unbalanced diets, habits of consuming instant foods, and a lack of understanding among parents regarding their children’s nutritional needs. Through this activity, lecturers and students conducted nutrition education, interactive discussions, and assistance in preparing healthy menus that are in accordance with the needs of early childhood and Islamic values. The results of the community service showed an increase in parents’ and educators’ understanding of the importance of balanced nutrition and an increase in families’ awareness of forming healthy eating habits for children from an early age. This activity is expected to become a model for collaborative community service by lecturers and students that is sustainable and has a direct impact on improving the health of early childhood